DO QUE SÃO FEITAS TODAS AS COISAS: UMA ABORDAGEM DE DEMÓCRITO AO MODELO PADRÃO - Silva, Edna de Souza da (2021)
In a quali-quantitative approach in educational research, the results of the application of a teaching proposal on the structure of matter for High School are analyzed, focusing on the models proposed for the atom and how they changed over time. The theorical reference used is the Meaningful Learning attributed to David Ausubel. The research was developed by an educational intervention carried out in Celicilano Abel de Almeida Public High School, located in São Mateus-ES. The research involved students of the third year through the application of a didactic sequence based on a Potentially Meaningful Teaching Unit, according to Marco Antônio Moreira. For methodological development, several didactic resources and strategies to motivate students were used, such as texts, games and films. After the application of the didactic sequence, the results of the tests, the analysis of the concept maps, as well as the interaction and participation of the students, provided evidence of meaningful learning and that the material used is potentially meaningful.